PSYCHOMETRIC PROPERTIES OF TRAVELERS NEEDS QUESTIONNAIRE (TNQ) - Ļevina, Jeļena; Koļesņikova, Jeļena; Kanonire, Tatjana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The purpose of this research was to develop the Travelers Needs Questionnaire (TNQ), which measures travelers’ needs, and to determine its psychometric properties. The TNQ was developed for travelers with native Russian language from different countries: Russia, Belarus, Ukraine, the Baltic States. The sample consisted of 237 participants aged from 17 to 68 years (26.2 % male, 73.8 % female, mean age M = 30.49, SD = 9.21). The factorial validity of the TNQ was established using principal components analysis with varimax rotation; this yielded seven factors: Professional Realization, Pilgrimage, Personal Development, Cultural Development, Sport, Physical Hedonism and Communication. All the TNQ scales had high internal consistency. The reaction and discrimination indices satisfied the accepted psychometric criteria. The further stage of the TNQ development would be the confirmatory factor analysis in broader international sample, the concurrent and convergent validity establishing, and test-retest reliability examination.